Pengaruh Brand Image dan Product Knowledge terhadap Purchase Intention dengan Green Price sebagai Moderating Variabel pada Produk the Body Shop di Surabaya - Ira Ningrum Resmawa (Jurnal Aplikasi Manajemen, Ekonomi dan Bisnis, 2017)
The focus of this research is to determine The Effect of Brand Image and Product Knowledge on Purchase Intention Moderated by Green Price the Body Shop Product in Surabaya. The results suggest that brand image has a significant influence on purchase intention The Body Shop product. Product knowledge has a significant influence on purchase intention on the The Body Shop Product. Green Price was not able to significantly moderate the effect of product knowledge on purchase intention The Body Shop Product. Green Price was shown to negatively moderate the influence of brand image on purchase intention, but not able to moderate the influence of product knowledge on purchase intention.